2016
DOI: 10.2527/jas.2015-9644
|View full text |Cite
|
Sign up to set email alerts
|

Litter-of-origin trait effects on gilt development1

Abstract: The preweaning litter environment of gilts can affect subsequent development. In a recent experiment designed to test the effects of diet on gilt development, litter-of-origin traits including individual birth weights, immunocrits (a measure of colostrum intake), sow parity, number weaned, and individual weaning weights were collected for approximately 1,200 gilts that were progeny of approximately 300 sows. Subsequently, BW, LM area, and backfat were measured at 100 d of age and at 28-d intervals until slaugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…A decreased farrowing-to-mating interval decreases the total number of piglets born [ 23 ] and PBA at subsequent parity. Meanwhile, low prolific gilts may be associated with having litter of origin problems, such as low birth weight [ 24 ]. Therefore, our study suggests that differences in farm effects can affect patterns of reproductive performance in both H-prolific and L-prolific sows.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased farrowing-to-mating interval decreases the total number of piglets born [ 23 ] and PBA at subsequent parity. Meanwhile, low prolific gilts may be associated with having litter of origin problems, such as low birth weight [ 24 ]. Therefore, our study suggests that differences in farm effects can affect patterns of reproductive performance in both H-prolific and L-prolific sows.…”
Section: Discussionmentioning
confidence: 99%
“…The relative protein content of EAAC1, GLT-1, GTRAP3-18, GS, and β-catenin in liver homogenates was detected using antibodies as described previously (Brown et al 2009 ; Miles et al 2015 , 2016 ). For ARL6IP1, an antibody raised against the human ortholog (see below) was validated for the detection of cattle ARL6IP1 using a standard pre-hybridization regimen (Xue et al 2011 ; data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…The birth weight and preweaning growth rate of piglets that will become replacement gilts are characteristics of litter-of-origin for subsequent reproductive performance of sows in later life [44]. Higher preweaning growth in replacement gilts is associated with a lower age at puberty.…”
Section: Reviewmentioning
confidence: 99%